Role of DNA Methylation in Mediating Genetic Risk of Psychiatric Disorders - Starnawska, Anna; Demontis, Ditte (Frontiers in Psychiatry, 2021)
Psychiatric disorders are common, complex and heritable conditions estimated to be the leading cause of disability worldwide. The last decade of research in genomics of psychiatry, performed by multinational and multicenter collaborative efforts on hundreds of thousands of mental disorder cases and controls, provided invaluable insight into genetic risk variants of these conditions. With increasing cohort sizes more risk variants are predicted to be identified in the near future, but there appears to be a knowledge gap in understanding how these variants contribute to pathophysiology of psychiatric disorders. Majority of identified common risk SNPs are non-coding, but are enriched in regulatory regions of the genome. It is therefore of great interest to study impact of identified psychiatric disorders’ risk SNPs on DNA methylation, the best studied epigenetic modification, playing a pivotal role in regulation of transcriptomic processes, brain development and functioning. This work outlines the mechanisms through which risk SNPs can impact DNA methylation levels and provides summary of current evidence on role of DNA methylation in mediating genetic risk of psychiatric disorders.